On minimizing objective and KKT error in a filter line search strategy for an interior point method - Costa, M. Fernanda P. (2011)
This paper carries out a numerical study of filter line search strategies that aim at minimizing the objective function and the Karush- Kuhn-Tucker (KKT) vector error in order to encourage global convergence of interior point methods. These filter strategies are implemented in an infeasible primal-dual interior point framework for nonlinear programming. First, we propose a filter that has four components measuring primal feasibility, complementarity, dual feasibility and optimality. The different measures arise from the KKT conditions of the problem. Then, we combine the KKT equations defining a different two-dimensional filter technique. The versions have in common the objective function as the optimality measure. The primary assessment of these techniques has been done with a well-known collection of small- and medium-scale problems.